Clinical efficacy of probiotic mouthwash in the treatment of gingivitis patients in Himachal population - Vikas Jindal; Neha Mahajan; Amit Goel; Rupinder Kaur; Atin Mahajan; Puja Thakur Malhotra (Wolters Kluwer Medknow Publications, 2017)
This study was conducted to analyze the changes in gingival health in patients treated with probiotic containing mouth rinse. Thirty volunteers between 20 and 35 years were randomly divided into two groups. While one group was given placebos, the other was given probiotic mouth rinse for 14 days. The volunteers were instructed to swish the mouth rinse for 60 s twice a day. Intergroup comparison of the plaque scores (baseline-14 days) showed there was statistically significant difference in the mean plaque scores between the placebos group (0.14) (P ≤ 0.05) and the test group (0.42) (P ≤ 0.05) and a statistically significant difference in the mean gingival scores from baseline-14 days between the placebos group (0.9) (P ≤ 0.05) and the test group (0.38) with (P ≤ 0.05). Despite the short period for which the probiotics mouthwash was used by the patients, substantial improvement in gingival health of patients was observed in the study.